2014
DOI: 10.1080/00221309.2014.964658
|View full text |Cite
|
Sign up to set email alerts
|

Unique Contributions of Metacognition and Cognition to Depressive Symptoms

Abstract: This study attempts to examine the unique contributions of "cognitions" or "metacognitions" to depressive symptoms while controlling for their intercorrelations and comorbid anxiety. Two-hundred-and-fifty-one university students participated in the study. Two complementary hierarchical multiple regression analyses were performed, in which symptoms of depression were regressed on the dysfunctional attitudes (DAS-24 subscales) and metacognition scales (Negative Beliefs about Rumination Scale [NBRS] and Positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 14 publications
1
13
0
1
Order By: Relevance
“…However, in this study we examined the individual contributions of both domains of negative metacognitive beliefs (negative beliefs about uncontrollability and harm, negative beliefs about the interpersonal and social consequences of rumination) that feature in the metacognitive model of depression, whereas Yilmaz et al . () entered the negative metacognitive beliefs as a unitary construct. Our analysis revealed that only negative beliefs about the uncontrollability and harm made a significant contribution to the final model.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…However, in this study we examined the individual contributions of both domains of negative metacognitive beliefs (negative beliefs about uncontrollability and harm, negative beliefs about the interpersonal and social consequences of rumination) that feature in the metacognitive model of depression, whereas Yilmaz et al . () entered the negative metacognitive beliefs as a unitary construct. Our analysis revealed that only negative beliefs about the uncontrollability and harm made a significant contribution to the final model.…”
Section: Discussionmentioning
confidence: 73%
“…The results from the hierarchical linear regression cross‐validate those obtained by Yilmaz et al . (), such that the block of metacognitive beliefs was able explain additional variance in depressive symptoms after controlling for dysfunctional attitudes. However, in this study we examined the individual contributions of both domains of negative metacognitive beliefs (negative beliefs about uncontrollability and harm, negative beliefs about the interpersonal and social consequences of rumination) that feature in the metacognitive model of depression, whereas Yilmaz et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, PB constitute an important part of the metacognitive model of depression (Wells et al., ; Yilmaz, Gençöz, & Wells, ). PB have been assumed to play an important role in the onset of depression as a link between rumination and depression (Huntley & Fisher, ; Weber & Exner, ).…”
Section: Discussionmentioning
confidence: 99%